IMPACT OF SEASONAL CHANGES ON MASTITOGEN AND N-ACETYL-Β-D-GLUCOSAMINIDASE ACTIVITY IN KARAN FRIES COW - R. Selvarani (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The  activity  of  N-acetyl-β-d-glucosaminidase  (NAGase)  in  milk  serves  as an indicator of mammary tissue damage and bovine mastitis. This study aimed to investigate the correlation between NAGase levels in both milk and plasma and the pathogens responsible for mastitis across different seasons. A total of 92 early-lactation KF cows maintained at the Livestock Research Centre, NDRI, Karnal, were screened for subclinical mastitis using the California Mastitis Test. From the positive cases, eight milk samples were collected in each season (thermoneutral, winter, and summer) for bacteriological and enzyme analysis. Bacteriological examination was performed to identify major pathogens, and NAGase levels were estimated using a commercial ELISA kit. Climatic parameters were recorded, and the Temperature Humidity Index (THI) was calculated to assess environmental stress. The data were analyzed using one-way ANOVA, which revealed that no significant seasonal variation was observed in milk and plasma NAGase activity in cows affected by either pathogen. Furthermore, no significant difference was found between mastitogens and milk enzyme levels.The stable NAGase activity across seasons suggests its usefulness as a reliable biomarker for monitoring udder health and subclinical mastitis in dairy cattle.